Massive vagal schwannoma in an 11‐year‐old girl. Issue 11 (10th November 2021) - Feit, Noah Z.; Fitzgerald, Conall W. R.; Mclean, Tim; Wong, Richard J.
Abstract: We describe an unusual case of a young girl presenting with a large vagal schwannoma necessitating a transcervical‐mandibulotomy approach for total tumor resection. The presentation is unique due to the size of the lesion, the patient's age, the operative approach, and molecular pathology. Abstract : Vagal schwannomas are rare peripheral nerve sheath tumors arising from the vagus nerve. They are typically diagnosed in adulthood. We describe an atypical case in terms of size of the lesion, patient age, surgical approach, and molecular pathology.